Strategi Branding dalam Promosi Penjualan Produk Pertanian Olahan PT. Hatten Bali untuk Pasar Pariwisata Indonesia - I Ketut Surya Diarta; Putu Widhianti Lestari; Ida Ayu Putu Citra Dewi (Universitas Udayana, 2016)
Branding becomes inevitable in sales promotion strategy of products and services in the era of globalization. However, the difficult challenge of agricultural products branding related to standardization because it involves a biological process that can not be fully controlled. Moreover, if the intended target market is specific to the tourism market.This paper discusses branding strategy used by agribusiness company PT. Hatten Bali in promoting wine processed